Effect of weed control methods and phosphorus fertilization on growth and yield of clusterbean - Kanwar, Krishna; Yadav, S.S.; Verma, H.P.; Yadav, L.R.; Shivran, A.C. (Annals of Agricultural Research, 2016)
A field experiment entitled "Efficacy of herbicidal weed control in clusterbean at varying levels ofphosphorus" was conducted at Agronomy Farm, S.K.N. College of Agriculture, Jobner (Rajasthan)during kharif season of 2013. The results indicated that two HW at 20 and 40 DAS significantlyincreased plant stand per meter row length, plant height, number of branches per plant, dry matteraccumulation per meter row length, number of pods per plant, number of grains per pod, testweight, seed, stover and biological yield and it remained at par with one HW at 20 DAS andapplication of imazethapyr @ 100 g/ha. Results further indicated that the application of phosphorus@ 60 kg/ha significantly increased plant height, number of branches per plant, dry matteraccumulation, number of pods per plant, number of grains per pod, test weight, seed, stover andbiological yield and remained at par with the application of phosphorus @ 40 kg/ha. However,plant stand per meter row length remained materially unchanged under different treatments ofphosphorus.